A review of flavour formation in continuous beer fermentations - Brányik, Tomáš (2008)
The attractive prospect of a continuous beer fermentation system consists mostly of the accelerated transformation of wort into beer. Although continuous beer fermentation has been studied as a promising technology for several decades, the number of industrial applications is still limited. The major obstacle hindering the extensive industrial exploitation of this technology is the difficulty in achieving the correct balance of sensory compounds in the short time typical for continuous systems. This paper offers an integral view on the particularities of continuous systems, which may impart beer a sensorial character distinct from conventionally fermented counterparts. The main groups of flavour active compounds are discussed from the perspective of possible control strategies by means of process parameters and strain selection.